Pengembangan Sistem Informasi Manajemen Barang (Studi Pada Toko Kertas MBC) - Double Win Yusuf Rais; Satrio Agung Wicaksono; Welly Purnomo (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
MBC Paper Shop is a company engaged in retail, selling and buying paper and office stationery (ATK). This company is still carrying out its operational activities manually, so that a problem arises in companies that are in the management of goods, which still use paper for recording, then the irregularity of the officers in keeping the transaction file archives, and making transaction notes is still done manually using paper. note. With these problems, a solution has emerged in the form of developing artifacts, namely goods management information systems that can help solve problems found. Artifact creation is implemented through the SDLC approach with the Waterfall method, on the website platform. In the analysis stage, 17 functional requirements were obtained. At the system design stage by applying OOAD (Object Oriented Analysis and Design), there were 6 controller classes and 4 model classes. In the implementation stage, the system uses the MVC method by implementing the Code Igniter framework as the system architecture. And in the last stage, namely the testing phase, testing the functional validation of the system to the user, the valid results are obtained 100 percent, and in the User Acceptance Testing test for users, 100 percent test results are obtained, that the user has received the system built. In this study, producing artifacts in the form of goods management information systems in warehouses that have features and functions according to user needs and have been tested on users.